PENGARUH RESIKO KREDIT TERHADAP PROFITABILITAS PADA PT. BANK NEGARA INDONESIA (Persero) Tbk. - Hairul Imam; Aliah Pratiwi; Alwi (Jurnal Ilmiah Satyagraha, 2025)
This research aims to determine the effect of credit risk on profitabilityat PT. Bank Negara Indonesia TBK. The instrument for this research is using thebalance sheet and profit and loss report at PT. Bank Negara Indonesia TBK from2014-2023. Meanwhile, the sampling technique used is purposive sampling, thecriteria are based on the availability of up-to-date data and research variabledata to be used. The data in this research was processed using SPSS. Thehypothesis testing method uses a significance level of 5%. The research resultsshow that Non-Performing Loans (NPL) have a significant effect on PT's ReturnOn Equity (ROE). Bank Negara Indonesia Tbk.